Contribuição ao método de captura de insetos por meio de armadilha luminosa, para obtenção de exemplares sem danos morfológicos - Fiuza Ferreira, Paulo Sérgio; dos Santos Martins, David (Revista Ceres, 2025)
Tn view of the difficulties of obtaining undamaged insect specimens via lighttrap collections, a new type of collection receptacle was developed for use with the «Luiz de Queiroz» — type light trap. To illustrate the effectiveness of this development, in a series of 35 nightly collections, 95% of the specimens collected were in a perfect condition.